Problematic aspects of trade manufacturing chains branding - Dobrovolska, Kateryna; Kovalchuk, Svitlana (Technology audit and production reserves, 2019)
The object of research is branding in production and trade chains. In the process of literary analysis, the authors found that most scientists are focused on the concept of supply chain management. But the state and degree of development of issues of formation and management of trade and production chains of enterprises, as well as branding in these chains are not adequately reflected in modern scientific literature. Given the importance and necessity of solving certain issues and problems, the authors dedicated their research to this topic. In the course of the research, an author's approach to the interpretation of the concept of «brand» is formed on the basis of scientific generalization. An author's definition of the concept of «brand» is obtained, by which the authors understand a clearly identified symbol, which for the consumer is not only informational sublimates (and/or a stable emotional impulse), but also an additional utility relative to competitor goods. This is due to the fact that the study clarifies the definition of the concept of «branding» from the perspective of the decomposition of the production and trade chain. The approach proposed in this work allows one to take into account the relationship and mutual influence of production and trading activities and to obtain a synergy effect from the use of branding throughout the entire production and trade chain. Thanks to this, the term «brand» is understood to mean a clearly identified symbol, which for the consumer is not only informational sublimates (and/or a stable emotional impulse), but also an additional value relative to competing goods. This together determines the consumer's choice in favor of the carrier of this brand. Understanding this ensures the formation of additional value at each stage of branding, strengthens the competitive position of the brand owner and improves branding. The next stage of the research, the authors determine the construction of the branding mechanism in production and trade chains. The mechanism should be based on the formation of planning processes unified for all markets and products, terminology databases, data structures for strategic analysis, strategic models and programs.